2018
DOI: 10.3389/fnins.2018.00667
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of Surface Electromyogram Suggest That Dry Immersion Relieves Motor Symptoms in Patients With Parkinsonism

Abstract: Dry immersion (DI) is acknowledged as a reliable space flight analog condition. At DI, subject is immersed in water being wrapped in a waterproof film to imitate microgravity (μG). Microgravity is known to decrease muscle tone due to deprivation of the sensory stimuli that activate the reflexes that keep up the muscle tone. In contrary, parkinsonian patients are characterized by elevated muscle tone, or rigidity, along with rest tremor and akinesia. We hypothesized that DI can diminish the elevated muscle tone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…The study enrolled 20 subjects with PD, 13 men and seven women. These subjects have participated in our previously published studies (Meigal et al, 2018(Meigal et al, , 2021aMiroshnichenko et al, 2018), where one can find their individual clinical and anthropological characteristics and medication. General characteristic of the subjects is presented in Table 1.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study enrolled 20 subjects with PD, 13 men and seven women. These subjects have participated in our previously published studies (Meigal et al, 2018(Meigal et al, , 2021aMiroshnichenko et al, 2018), where one can find their individual clinical and anthropological characteristics and medication. General characteristic of the subjects is presented in Table 1.…”
Section: Participantsmentioning
confidence: 99%
“…The condition of DI was induced by means of the "Medical Facility of Artificial Weightlessness" (MEDSIM, Center for Aerospace Medicine and Technologies, State Scientific Center of Russian Federation "Institute of Biomedical Problems, " Moscow, Russia) housed in Petrozavodsk State University (Petrozavodsk, Russia). A detailed description of the procedure of DI applied to the group of PD subjects is available in our earlier papers (Meigal et al, 2018(Meigal et al, , 2021aMiroshnichenko et al, 2018). The short-term DI session lasted 45-min.…”
Section: The DI Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before a magnetic resonance imaging (MRI) scan and clinical assessments, the PD patients were asked to withdraw from all anti-Parkinson medications for approximately 12 h. The Unified Parkinson’s Disease Rating Scale (UPDRS), the Hoehn and Yahr disability scale (HY) and the Mini-Mental Sate Examination (MMSE) were obtained from each PD subject. Psychiatric or other neurological illnesses constituted exclusion criteria as Miroshnichenko et al reported ( Miroshnichenko et al, 2018 ). All subjects were free of hypothyroidism, epilepsy, drug/alcohol/nicotine abuse, and free of kidney or liver disease.…”
Section: Methodsmentioning
confidence: 99%
“…A program of analog microgravity (μG) modeled with “dry” immersion (DI) was recently shown to reduce the scores of muscle rigidity and depression in PD ( Meigal et al, 2018 ). Furthermore, the regularity of the surface electromyogram, indicative of tremor reduction, was decreased after a single short DI session ( Miroshnichenko et al, 2018 ). Programs of common water immersion combined with exercises exerted similar beneficial effect on cognition and motion in elderly people without PD ( Kim et al, 2018 ), presumably due to more efficient cortical processing of somatosensory signals ( Sato et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%